Rate of convergence for Szász-Bézier operators - Gupta, Vijay (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We estimate the rate of convergence for functions of bounded variation for the Bezier variant of the Szasz operators $S_{n, α}(f, x)$. We study the rate of convergence of $S_{n, α}(f, x)$ for the case $0 < α < 1$.